UPDATE ON THE ROLE OF AUTOLOGOUS HEMATOPOIETIC STEM CELL TRANSPLANT IN FOLLICULAR LYMPHOMAS - Mónica Cabrero; Alba Redondo; Alejandro Martin; Dolores Caballero (Mediterranean Journal of Hematology and Infectious Diseases)
Follicular lymphoma (FL) remains incurable despite advances in new strategies of treatment, including monoclonal antibodies (MoAb). Except for early stages, FL is characterized by responses to treatments and systematic relapses. The main objective in this disease is to achieve a better progression free survival (PFS) and to increase overall survival (OS), mainly in young patients. In order to improve the results of conventional chemotherapy, autologous stem cell transplant (ASCT) is a feasible treatment in these patients. In this moment, ASCT is not recommended as first line treatment, except for transformed FL, but is a good strategy as salvage therapy with an improved PFS and OS. New drugs have been introduced to enhance responses of ASCT, but nowadays they are not part of conventional conditioning regimen.